The case for a medication first approach to the treatment of opioid use disorder. (4th July 2019) - Winograd, Rachel P.; Presnall, Ned; Stringfellow, Erin; Wood, Claire; Horn, Phil; Duello, Alex; Green, Lauren; Rudder, Tim
ABSTRACT: Background : The opioid addiction and overdose crisis continues to ravage communities across the U.S. Maintenance pharmacotherapy using buprenorphine or methadone is the most effective intervention for Opioid Use Disorder (OUD), yet few have immediate and sustained access to these medications. Objectives : To address lack of medication access for people with OUD, the Missouri Department of Mental Health began implementing a Medication First (Med First) treatment approach in its publicly-funded system of comprehensive substance use disorder treatment programs. Methods : This Perspective describes the four principles of Med First, which are based on evidence-based guidelines. It draws conceptual comparisons between the Housing First approach to chronic homelessness and the Med First approach to pharmacotherapy for OUD, and compares state certification standards for substance use disorder (SUD) treatment (the traditional approach) to Med First guidelines for OUD treatment. Finally, the Perspective details how Med First principles have been practically implemented. Results : Med First principles emphasize timely access to maintenance pharmacotherapy without requiring psychosocial services or discontinuation for any reason other than harm to the client. Early results regarding medication utilization and treatment retention are promising. Feedback from providers has been largely favorable, though clinical- and system-level obstacles to effective OUD treatment remain. Conclusion : Like the Housing First model, Medication First is designed to decrease human suffering and activate the strengths and capacities of people in need. It draws on decades of research and facilitates partnerships between psychosocial and medical treatment providers to offer effective and life-saving care to persons with OUD.